Efeito da composição nas isotermas de sorção e características do biscoito de polvilho - Ribeiro, Kelly Menezes (2006)
The sour manioc biscuit is a crispy product, having as a basic raw material, sour manioc flour. After baking, according to its final moisture content, the biscuit will be in the vitreous state. Depending on the storage conditions it can suffer alterations through moisture, as, for instance, alteration of the texture, reducing its shelf-life. This present work aime to study the effect of the composition and storage conditions (temperature and relative humidity) on the stability of the manioc flour biscuit. The experimental was done in the Laboratories of Food Microstructure and of Grains and Cereals, in the Food Science Department at the Federal University of Lavras, MG. In the study of the effect of the composition of the biscuits on kinetics and sorption isotherm and on the physical-chemistries analyses, eight different formulations were used for their preparation. In these, the same percentage of sour manioc flour was used, being analyzed the effect of the variables: water, fat and salt in relation to the amount of sour manioc flour, a 2x2x2 factorial plan was used. The curve of the kinetics and the isotherms was obtained using eight storage relative humidities at 14ºC, 30ºC and 40ºC. the different formulations used in he preparation of the biscuits affected the color and physical-chemical properties of these biscuits. The model Peleg was the one that better it was adjusted for whole range of temperatures and relative humidities studied. The elevation of the salt and water content made the sour manioc biscuits, in general, more unstable during their, and the elevation of the vegetable fat content contributed to the increased stability of the biscuits. The biscuits stored the temperatures of 14ºC and 30ºC were more stable than those stored at 40ºC at the same relative humidity. Is is concluded that the composition of the biscuits and the storage conditiond affect their stability during their shelf-life.